GPX2 overexpression indicates poor prognosis in patients with hepatocellular carcinoma. Issue 6 (June 2017) - Liu, Ting; Kan, Xue-feng; Ma, Charlie; Chen, Li-li; Cheng, Tian-tian; Zou, Zhen-wei; Li, Yong; Cao, Feng-jun; Zhang, Wen-jie; Yao, Jing; Li, Pin-dong
Glutathione peroxidase 2 has important role of tumor progression in lots of carcinomas, yet little is known about the prognosis of glutathione peroxidase 2 in hepatocellular carcinoma. Glutathione peroxidase 2 expression was assessed by immunohistochemistry in hepatocellular carcinoma tissues. The association between glutathione peroxidase 2 expression with clinicopathological/prognostic value was examined. Glutathione peroxidase 2 overexpression was correlated with alpha-fetoprotein level, larger tumor, BCLC stage, and tumor recurrence. Kaplan–Meier analysis showed that glutathione peroxidase 2 was an independent predictor for overall survival and time to recurrence. glutathione peroxidase 2 overexpression was correlated with poor prognosis in patient subgroups stratified by tumor size, differentiation, tumor–node–metastasis, and BCLC stage. Moreover, stratified analysis showed that tumor–node–metastasis stage-I patients with high glutathione peroxidase 2 expression had poor prognosis than those with low glutathione peroxidase 2 expression. Additionally, combination of glutathione peroxidase 2 and serum alpha-fetoprotein was correlated with prognosis in hepatocellular carcinoma. In conclusion, glutathione peroxidase 2 overexpression contributes to poor prognosis of hepatocellular carcinoma patients and helps to identify the high-risk hepatocellular carcinoma patients.